Orientation of prehistoric monuments in Britain : a reassessment - Marshall, Alistair (Archaeopress Archaeology, 2021)
Reassesses major axial alignment at many megalithic ritual and funerary monuments (Neolithic to Bronze Age) in Britain and Ireland, not in terms of abstract astronomical concerns, but as an expression of repeated seasonal propitiation involving community, agrarian economy and ancestry in an attempt to mitigate variable environmental conditions.